A Cross Entropy Minimization based Beam Selection for Time-Variant mmWave Beamspace MU-MIMO Communication System - Pal R.; Sarawadekar K. (My University, 2025)
The millimeter wave beamspace multi-user MIMO communication system suffers from high radio frequency complexity. However, RF complexity can be reduced by deploying a beam selection algorithm at access point without significant loss in the performance. Therefore, we proposing a novel time-variant beam selection algorithm for such system. It follows a metaheuristic approach to find the near-to-optimal solution and outperforms the existing time-variant beam selection algorithm. © 2019 IEEE.